2019
DOI: 10.1002/aic.16805
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and local mass transfer characterization under gas–liquid–liquid slug flow in a rectangular microchannel

Abstract: Gas-liquid-liquid three-phase slug flow was generated in a glass microreactor with rectangular microchannel, where aqueous slugs were distinguished by relative positions to air bubbles and organic droplets. Oxygen from bubbles reacted with resazurin in slugs, leading to prominent color changes, which was used to quantify mass transfer performance. The development of slug length indicated a film flow through the corner between bubbles and the channel wall, where the aqueous phase was saturated with oxygen trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 49 publications
1
29
0
Order By: Relevance
“…Understanding into transport characteristics within gasliquid-liquid flow in microreactors is of vital importance for the design, operation and optimization of such microreactor systems for their promising applications in the abovementioned fields. Compared with the extensive gas-liquid and liquid-liquid two-phase flow studies in microreactors [23,[45][46][47][48], limited research has been paid to the case of gas-liquid-liquid microflow [11,12,19,29]. A considerable fraction of the literature work in the latter case was focused on hydrodynamics therein [13,14,17,18,49,50], and few on the investigation of mass transfer property [12,14] and the preliminary exploration of the potential applications [21,29,30,38].…”
Section: Article Highlightsmentioning
confidence: 99%
See 3 more Smart Citations
“…Understanding into transport characteristics within gasliquid-liquid flow in microreactors is of vital importance for the design, operation and optimization of such microreactor systems for their promising applications in the abovementioned fields. Compared with the extensive gas-liquid and liquid-liquid two-phase flow studies in microreactors [23,[45][46][47][48], limited research has been paid to the case of gas-liquid-liquid microflow [11,12,19,29]. A considerable fraction of the literature work in the latter case was focused on hydrodynamics therein [13,14,17,18,49,50], and few on the investigation of mass transfer property [12,14] and the preliminary exploration of the potential applications [21,29,30,38].…”
Section: Article Highlightsmentioning
confidence: 99%
“…4b), which makes the whole mass transfer scenarios more complicated, especially for the gas transfer to the aqueous bulk (i.e., subsequently through the gas-oil interface, organic bulk, aqueous-oil interface and aqueous bulk). In a most recent work, Liu et al [12] revealed that the film flow through the gap between bubbles and the microchannel wall contributed significantly to the gas transferring into the continuous phase, and an alternating bubble/droplet sub-regime ( Fig. 1a (i)) is preferred towards mass transfer optimization.…”
Section: Heterogeneous Catalysismentioning
confidence: 99%
See 2 more Smart Citations
“…Liu et al 22 studied the characteristics of bubble splitting under three-phase ow in a double T-junction microchannel, revealing the critical breaking length and the size of the sub-bubble/slug. More recently, Liu et al 23 further investigated the effects of the threephase slug sub-regime ow on hydrodynamics and local mass transfer, conrming that the alternate bubble and droplet ow is in favor of mass transfer.…”
Section: Introductionmentioning
confidence: 99%